Does Hybrid Mathematics Learning Evaluation Enhance Metacognitive Creative Problem-Solving? A Multi-Group Analysis by Gender - Mujib Mujib; Mardiyah Mardiyah (CV FOUNDAE, 2026)
Mathematics learning evaluation in hybrid learning environments is not only viewed as an assessment approach but also as a pedagogical strategy that facilitates students’ cognitive regulation and problem-solving processes. However, empirical evidence on the impact of hybrid mathematics learning evaluation on students’ metacognitive engagement in creative problem-solving, particularly regarding gender differences, remains limited. This study aims to explore the structural relationship between hybrid mathematics learning evaluation and metacognitive creative problem-solving, including gender differences. A partial least squares structural equation modeling (PLS-SEM) approach was used to collect data from 147 undergraduate mathematics students. Overall, the findings indicate a positive relationship between hybrid mathematics learning evaluation and metacognitive creative problem-solving across the full sample. In terms of gender differences, although the relationship is significant for both groups, it is stronger for male students. However, multi-group analysis revealed no significant difference in structural relationships between males and females, indicating model invariance. This study highlights the value of developing hybrid mathematics evaluation strategies to support students’ metacognitive abilities in creative problem-solving